(untitled) (Annals of Medical Research, 2021)
Aim: To determine the ability of ileocolic artery (ICA) and ileocolic vein (ICV) diameter measurements in the diagnosis of acute appendicitis.Material and Methods: ICA, ICV, abdominal aorta (AA) and inferior vena cava (IVC) diameters were recorded in 123 patients. Patients were grouped according to the presence of acute appendicitis clinically-radiologically. The receiver operating characteristic (ROC) curves were constructed to obtain the cutoff values ​​in terms of differentiation of appendicitis and control groups.Results: ICA, ICV, ICA/AA and ICV/IVC measurements differed significantly between the appendicitis (n=75) and control (n=48) groups (p 0.001, p 0.001, p =0.003, p =0.006). The best cutoff values for ICA and ICV to differentiate appendicitis from the control group were 2.92 mm and 4.28 mm, respectively. The ICA, with a cut-off point based on the ROC curve, of 2.92 mm provided a sensitivity of 70.7%, and a specificity of 70.8%. Applying the cut-off point of 4.28 mm for ICV, generated a sensitivity of 80%, and a specificity of 72.9%.Conclusion: Measurements of the ICA and ICV diameter in computed tomography (CT) is a promising application for determining acute appendicitis. This preliminary study suggests ICA and ICV diameter measurements could contribute as an alternative parameter to major radiological evidence in the diagnosis of acute appendicitis.Keywords: Ileocolic artery; ileocolic vein; acute appendicitis; abdominal; computed tomography.